Barcode reader programme: software development for dining hall / Muhamad Sukri Kholil - Kholil, Muhamad Sukri (2004)
This project focuses on implementing a barcode reader programme in dining hall's college in UiTM. The programme is a One Dimensional (1D) barcode system, is developed to improve the conventional attendance system used in College and also to help improving the services in the dining hall. By scanning the student's matric card, the system can determine and analyse information. It is targeted that the efficiency of the attendance system in College will increase. This system was tested and the result shows that the system works correctly where it can record and present the detailed analysis just by scanning the student's matric card by the use of barcode scanner. The development of the code program for this project is done using the Microsoft Visual Basic 6.0. The Microsoft Access database is used for the database record.